Socioeconomic effects of Oyo state government COVID-19 palliatives on poultry farmers - Akande, A.; Ayedun, B. (Universe Publishing Group - UniversePG, 2023)
This study interviewed 349 poultry farmers that benefited from government poultry feed input palliatives meant to help them to contain the negative effects of COVID-19 of hunger, food insecurity, and poverty. Demographic results revealed that both males and females are involved in poultry farming; the average age of poultry farmers was 45 years, with an average family size of five. The average years of education were 13, equivalent to JSS 3 in the Nigerian education system. Types of poultry show that 49% of the poultry farmers reared broilers, 42% layers, and 1% cockerels, while 8% reared both broilers and layers. Production characteristics reveal that 55.1% of the poultry farmers were members of an association like the Poultry Association, 78.5% benefited from government training, and 98% experienced reduced production costs on their poultry enterprise. The results show that reductions in the cost of production with government intervention were 30% of the total cost of production, and lower death was experienced among broiler enterprises compared to layer enterprises. The major benefits derived from the COVID-19 palliative included 39% of them experiencing increased farm income; 24.7% getting their cost of production reduced; 18.9% experiencing reduced hunger in their families, and 17.4% having increased output of bird produce through the palliative intervention. Using the Logit regression as an econometric model, the result for layer bird enterprises shows that Farm experience (p<0.1), and Increased production (p<0.05), among others, positively and significantly increased perception of hunger reduction by the beneficiaries; while the number of Birds owned (p<0.1), and Cost of medication (p<0.05) negatively and significantly reduced perception on hunger reduction by the beneficiaries. One broiler enterprise 12 explanatory variables statistically and significantly influence the decision of farmers on their perception of “hunger reduction”; the variables included those that positively and significantly influence farmer perception of reduced hunger. These are Education Squared (p<0.01), Poultry Association (p<0.05), % Cost Reduction (p<0.01), and Increased Production (p<0.01). Variables that statistically reduced perceptions on reduced hunger, among others, included Cost of Medication (p<0.01) and Production Cost/Bird (p<0.01). Therefore, government and nongovernmental organizations are recommended to push forward with interventions, especially focusing on identified factors, to strengthen the farmers’ capacity to battle against hunger and poverty.